1987
DOI: 10.1128/jb.169.9.4018-4023.1987
|View full text |Cite
|
Sign up to set email alerts
|

Western blot (immunoblot) analysis of the fimbrial antigens of Bacteroides nodosus

Abstract: The roles of the fimbrial subunit and the putative basal protein antigens in the (13,19,35,37). They are also involved in the serological K agglutination reaction (8,12,19,39), which has been used to divide B. nodosus isolates into at least eight serogroups and numerous subsidiary serotypes (6-8, 19, 32). These groupings are reflected in the patterns of immunity against different strains, in that the range of protection conferred by vaccination with either isolated fimbriae or whole cells is largely restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The antibodies generated by native pili reacted with many more strains on immunodot assays than on Western blot assay, suggesting that they recognized primarily structural epitopes that are lost on denaturation of the pili. These results are similar to those of recent work in which other bacterial pili show the dependence of pilus epitopes on the tertiary or quaternary structure of the pili (1,2,8,18,23,27,28). Conversely, antibodies against pilins and the 13-amino-acid pilin peptide did not recognize native pili from any of the strains, including the homologous strain, suggesting that, although these epitopes are conserved on native pili, they may exist in a different conformation or be otherwise inaccessible for antibody binding.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The antibodies generated by native pili reacted with many more strains on immunodot assays than on Western blot assay, suggesting that they recognized primarily structural epitopes that are lost on denaturation of the pili. These results are similar to those of recent work in which other bacterial pili show the dependence of pilus epitopes on the tertiary or quaternary structure of the pili (1,2,8,18,23,27,28). Conversely, antibodies against pilins and the 13-amino-acid pilin peptide did not recognize native pili from any of the strains, including the homologous strain, suggesting that, although these epitopes are conserved on native pili, they may exist in a different conformation or be otherwise inaccessible for antibody binding.…”
Section: Discussionsupporting
confidence: 89%
“…In order for Hib pili to have value as a vaccine, they must stimulate the formation of antibodies that protect against the majority of disease-producing Hib isolates. Previous studies of pili of several different bacteria have found strain-to-strain antigenic differences in pili to be an obstacle to their use as broadly effective vaccines (2,19,27). Despite this antigenic diversity, bacterial pili have been found by immunologic as well as amino acid and nucleotide sequence analysis (19,27) to contain highly conserved regions.…”
mentioning
confidence: 99%
“…Minor changes in primary structure may be associated with major changes in the 3-dimensional configuration, thereby exposing differing antigenic determinants. 41 These studies indicate that the molecular weight of the major pilin protein in various serotypes of B nodosus varies and that some serotypes that are widely separated antigenically have major pilin subunits of nearly identical molecular weight. Furthermore, use of the methods reported in this study yielded only single homogeneous pilin subunits within serotypes.…”
Section: Resultsmentioning
confidence: 87%